Layout Automation Techniques to Optimize Time-to-Market Factor - G S Meghana; Sheetal Kochrekar; Poornima Venkatasubramanian (EAI Endorsed Transactions on Cloud Systems, 2019)
With the ever growing demand for IPs in the domain of mobiles, 5G, and sensors for wearables and IoT applications, time to market becomes a crucial factor. There is always a need for delivering IPs to the competitive market in very less time without compromising on the quality. This necessitates the development of a reliable automation technique that can be easily integrated into the design cycle and Quality assurance flow of an IP. In this paper, we propose a generic automation flow for generating seed layouts for any technology node. The proposed flow reduces manual efforts and improves overallproductivity.